Coordinate transforms in kinematic changeable sets - Grushka, Ya. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
This work is devoted to the study of kinematic changeable sets ("abstract kinematics") that are equipped by different geometrical or topological structures, namely, by metric, topological, linear, Banach, Hilbert, and other spaces. Investigations in this direction may be interesting for astrophysics, because there exists the hypothesis that, on large scales of the Universe, the physical laws (in particular, the laws of kinematics) can be different from the laws acting in the neighborhood of our solar system.